1984
DOI: 10.1159/000199037
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Hyperplasia after Small Bowel Resection in the Rat: Dissociation from Endogenous Gastrin Levels

Abstract: Extensive small bowel resection produces pancreatic hyperplasia and increases plasma gastrin levels in the rat. Because gastrin is known as a trophic factor for the exocrine pancreas, we studied the effect of endogenous variations of gastrin induced by different gastric operations on the rat pancreas in both resected and transected animals. Vagotomy increased plasma gastrin level while antrectomy decreased it; pyloroplasty was without any effect. These gastric operations enhanced slightly but not significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Pancreatic hyperplasia, not hypertrophy, was shown to develop in rats after subtotal [20] or distal small-bowel resection [3] both in the presence and absence of hypergastrinemia [20]. We obtained similar results of pancreatic growth following distal smallbowel resection [14], In rats, therefore, the distal small bowel seems to contain inhibitory factors, too.…”
Section: Discussionsupporting
confidence: 59%
“…Pancreatic hyperplasia, not hypertrophy, was shown to develop in rats after subtotal [20] or distal small-bowel resection [3] both in the presence and absence of hypergastrinemia [20]. We obtained similar results of pancreatic growth following distal smallbowel resection [14], In rats, therefore, the distal small bowel seems to contain inhibitory factors, too.…”
Section: Discussionsupporting
confidence: 59%
“…The conclusion that the secretory capacity of the pancreas and its response to physiological stimuli may not be altered by the syndrome is supported by experimental studies in rats in which even hypersecretion and pancreatic hyperplasia have been observed [5,31]. On the other hand, a decreased duodenal activity of pancreatic enzymes in rats after small intestine resection suggesting pancreatic dysfunction was reported by Murillo et al [22] and Carreras et al [1].…”
Section: Pancreatic Secretion In Short Bowel Syndromementioning
confidence: 85%
“…Dembinski and Johnson [9] performed antrec tomy combined with exogenous administra tion of gastrin and provided further evi dence for gastrin as a trophic factor for the pancreas. However, in the studies of Oscarson et al [10], who showed adaptive pan creatic changes after BII gastrectomy, and in studies of Stock Damge et al [11], who found a trophic effect following subtotal small intestinal resection persisting after an trectomy, the trophic effect of gastrin was questioned. In our experiments, the reduc tion of gastrin-producing cells by distal gas tric resection supports the latter theory that gastrin does not play a major role in pan creatic trophism.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for gastrin as a trophic agent is given using an experi mental rat model [8,9], whereas this finding is not confirmed in other experiments [10,11].…”
mentioning
confidence: 82%